2006
DOI: 10.1017/s1047951105002398
|View full text |Cite
|
Sign up to set email alerts
|

Current insights regarding neurological and developmental abnormalities in children and young adults with complex congenital cardiac disease

Abstract: Over a decade ago, I co-authored a review in Cardiology in the Young regarding neurological outcomes following surgery for congenital cardiac disease.1In that review, I placed much emphasis on the conduct of cardiopulmonary bypass, and its role in neurodevelopmental disabilities. Much has been learned in the intervening years regarding the multifactorial causes of abnormal school-age development, in particular, the role of prenatal, perioperative, socioeconomic, and genetic influences. In this update, I will h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
239
1
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 294 publications
(247 citation statements)
references
References 94 publications
2
239
1
5
Order By: Relevance
“…Our findings extend the knowledge of long-term neurological impairment and mental health functional morbidities in the population with CHD. Although previous studies have reported elevated risks of adverse neurodevelopmental outcomes among individuals with CHD, including increased occurrence of depression, autism, and epilepsy compared with the general population, [6][7][8]19,[32][33][34][35] our study examined an older adult population to determine the later-life consequences of this neurological outcome. Although the underlying pathophysiological mechanisms are not completely understood, the potential etiologic factors appear multifactorial and consistent with previous findings within the neurodevelopmental scientific literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings extend the knowledge of long-term neurological impairment and mental health functional morbidities in the population with CHD. Although previous studies have reported elevated risks of adverse neurodevelopmental outcomes among individuals with CHD, including increased occurrence of depression, autism, and epilepsy compared with the general population, [6][7][8]19,[32][33][34][35] our study examined an older adult population to determine the later-life consequences of this neurological outcome. Although the underlying pathophysiological mechanisms are not completely understood, the potential etiologic factors appear multifactorial and consistent with previous findings within the neurodevelopmental scientific literature.…”
Section: Discussionmentioning
confidence: 99%
“…19,[37][38][39][40] Medical and surgical management of CHD, which may result in embolic events and brain injuries inducing cerebral ischemia, hemodilution, and postoperative low-cardiac output physiology, all may negatively contribute to decreased brain reserve. 7,32,33 For example, vascular brain injuries, including clinically silent strokes, have been observed both pre-and postoperatively in infants with CHD. 6 Hypoxemia affects the same cellular pathways and may enhance this effect.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite this increased survival, a high risk for neurodevelopmental co-morbidity persists [2]. Neurodevelopmental outcomes are characterized by a diverse spectrum of developmental delays and disabilities including impaired executive functions with the prevalence and severity increasing with the complexity of the CHD [3][4][5][6][7]. The etiology of these neurodevelopmental disorders is complex and several variables including pre-existing brain abnormalities and evolving factors in the perioperative period are believed to play a significant role [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Children with congenital heart disease (CHD) are at risk for developmental delays (DDs). [1][2][3][4] A characteristic pattern of a high prevalence of low-severity or combined disabilities in the areas of visual motor integration, language, motor skills, attention, executive function, and behavior has been described in multiple research studies. [5][6][7] Although many studies have reported outcomes near 1 year of age, no previous studies have obtained serial measures by using a consistent developmental assessment tool in young children throughout the first 3 years of life.…”
mentioning
confidence: 99%